Hha has a defined regulatory role that is not dependent upon H-NS or StpA - Solórzano, Carla; Srikumar, Shabarinath; Canals, Rocío; Juárez, Antonio; Paytubi, Sonia; Madrid, Cristina (Frontiers in Microbiology, 2015)
The Hha family of proteins is involved in the regulation of gene expression in enterobacteria by forming complexes with H-NS-like proteins. Whereas several amino acid residues of both proteins participate in the interaction, some of them play a key role. Residue D48 of Hha protein is essential for the interaction with H-NS, thus the D48N substitution in Hha protein abrogates H-NS/Hha interaction. Despite being a paralog of H-NS protein, StpA interacts with HhaD48N with higher affinity than with the wild type Hha protein. To analyze whether Hha is capable of acting independently of H-NS and StpA, we conducted transcriptomic analysis on the hha and stpA deletion strains and the hhaD48N substitution strain of Salmonella Typhimurium using a custom microarray. The results obtained allowed the identification of 120 genes regulated by Hha in an H-NS/StpA-independent manner, 38% of which are horizontally acquired genes. A significant number of the identified genes are involved in functions related to cell motility, iron uptake and pathogenicity. Thus, motility assays, siderophore detection and intra-macrophage replication assays were performed to confirm the transcriptomic data. Our findings point out the importance of Hha protein as an independent regulator in Salmonella Typhimurium, highlighting a regulatory role on virulence.